Why Are Companies Too Creative in Accounting? An Empirical Study in Slovakia - Jakub MICHULEK; Lubica GAJANOOVA (Communications of International Proceedings, 2023)
Financial accounting continues to face several difficulties with creative accounting. The issue of manipulation of financial statements needs to be examined not only from a financial, accounting, legal, or ethical point of view, but also from a psychological point of view. The aim of the research is to find out whether the size of the company has an impact on the motives leading to the use of creative accounting and the performance of creative accounting actions based on the request of a senior employee. Pearson's χ2 test was used in the study to determine the dependence of the researched variables in contingency tables. Correspondence analysis was then applied. The results demonstrated how the size of the business affects both the motives for creative accounting and the execution of such actions at the executive's request. The analysis of creative accounting from a psychological and managerial perspective in the Slovak Republic is what makes the research distinctive. The limitations of the research can be considered an incomplete balance of the research sample in terms of types of companies of different sizes. This is a difficult task because it is impossible to predict which of the approaching companies will fill out the questionnaire and which will not.
Keywords: Creative Accounting. Motives of Creative Accounting. Accounting. Employee Behaviour. Company size.